Cleaning potential of different air abrasive powders and their impact on implant surface roughness. (13th December 2019) - Matsubara, Victor H.; Leong, Bron W.; Leong, Marcus J. L.; Lawrence, Zacharij; Becker, Thomas; Quaranta, Alessandro
Abstract: Background: Implant surface roughness after air abrasive therapy has not been measured precisely in previous research. Debridement with air abrasion facilitates the mechanical removal of bacterial biofilms but may damage implant surfaces on a microscopic level. Purpose: This study aimed to investigate the cleaning potential of various air abrasive powders and their effect on titanium implant surfaces. Materials and Methods: Twenty implants coated with red ink were inserted into three‐dimensional printed circumferential bone defect models. Treatment was completed with three types of air abrasive powders: sodium bicarbonate (SB), glycine, and erythritol for 60 seconds. Water alone was used as control. The percentage of remaining ink was assessed using digital photography and graphic software. Implant surface topography/roughness was quantified using optical profilometry and examined via scanning electron microscopy. The microscopic analysis was performed at two implant areas: collar (Laser‐Lok surface) and threads. Results: The cleaned surfaces (%, mean ± SD) after treatment with SB, glycine, and erythritol accounted for 49.3 ± 3.6%, 33.1 ± 1.2%, and 25.1 ± 0.7%, respectively. Statistically significant differences were found between all groups ( P < .001). SB was the only powder that significantly increased the implant roughness ( S a ) on both the implant collar (1.53‐2.10 μm) and threads (3.53‐4.20 μm). Regardless of the abrasive powder used, the collar, emerging implant surfaces from the defect base, and surfaces beneath implants threads exhibited more post‐treatment residual ink. Conclusion: Large‐sized powder showed the greatest cleaning capacity, but caused more alterations to the implant surface. Glycine and erythritol displayed no significant changes in surface roughness, however, demonstrated a limited ink removal capacity.